ROLE OF AGRITHE ROLE OF AGRICULTURE IN THE ECONOMIC STRUCTURE OF SERBIA AND BUDGET SUPPORT FOR RURAL DEVELOPMENT OF KLADOVO MUNICIPALITYCULTURE IN THE ECONOMIC STRUCTURE OF SERBIA AND BUDGET SUPPORT FOR RURAL DEVELOPMENT OF KLADOVO MUNICIPALITY - Grujić Vučkovski, Biljana; Simonović, Zoran; Ćurčić, Nikola; Miletić, Vuk (Economics of Agriculture, 2022)
The purpose of writing the paper is the situation in agriculture in Serbia and the municipality of Kladovo, as well as the importance it achieves in the economic structure. At the level of Serbia, the importance of agriculture, forestry and fisheries (AFF) is analyzed through their contribution to gross domestic product (GDP) creation from 2016 to 2020, while for the municipality level the importance is determined by the amount of funds allocated in the local self-government unit (LSU) for the needs of agriculture from 2018 to 2020. The obtained results indicate a high share of AFF in GDP creation (6.3% during 2020) and a low share of budget funds in the total budget of the municipality for support of rural development (2.34% in 2020). The aim of this paper is to analyze the possibilities for further development of agriculture in the Republic and the Municipality. The paper uses methods of critical analysis of relevant literature, as well as descriptions for interpreting the results obtained by empirical research.